HYDRONIMS FORMED BY THE METHOD OF SYNTACTIC AND TRANSONIMIZATION - Majidova Shakhnoza Komilovna (Scholar Express Journal, 2024)
In the article, words are classified depending on the basis on which they are formed. The hydronyms of Surkhandarya are created by the method of composition and transonymization. Hydronymic determinants play an important role in the formation of hydronyms. Hydronomic identifiers are added to the words of various phrases, characterizing them to express the name of a water body and structure. It is the basis for the formation of hydronyms of combined and complex composition and denotes the type of reservoir.
Keywords: hydronym; composition; transonymization